A Novel Approach to the Operationalization of Corporate Local Embeddedness: Cultural Perspectives on Narratives as Indicators - Zsuzsanna PÁLFFY (European Journal of Interdisciplinary Studies)
Corporate embeddedness, the extent to which companies anchor themselves in a local context through political, economic, academic, social, and environmental connections, remains a key area of research in social and regional sciences. Due to the limited availability of secondary data on corporate relationships, measurement methods often rely on qualitative data. Corporate communication, especially CEO letters in annual reports, is a frequently neglected secondary data source that has grown in significance in meeting stakeholder expectations and providing insights into corporate strategies and operations. Despite the growing scholarly interest in CEO letters, little is known about embeddedness narratives and the cultural factors that influence them. Through an analysis of the cultural variations in embeddedness narratives found in CEO letters from the fashion and cosmetics industries, this study suggests a novel approach to operationalising corporate local embeddedness. The focus on these sectors is justified by the significant variations in embeddedness orientations across industries and the accessibility of relevant data. The study finds that CEO letters can serve as a complementary data source for assessing corporate embeddedness, as they reveal both local and global orientations. Using software-based content analysis, key themes and keywords were identified along the Quintuple Helix model, providing a structured approach to analysing embeddedness. The results highlight cultural influences, with reactive cultures emphasising social sustainability, while academic engagement challenges existing assumptions. In addition to reflecting corporate strategies, CEO letters offer insights into sectoral characteristics. However, more qualitative research is still required to fully comprehend a company’s level of embedding.